2008
DOI: 10.1007/s12185-008-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Severe degenerative change of multiple organs mediated by chronic active Epstein–Barr virus infection with infected T-cell expansion

Abstract: We here report the case of a young Japanese woman diagnosed with chronic active Epstein-Barr virus (EBV) infection. Intensive therapy with the CHOP regimen was partially able to control virus expansion, but various central nervous system symptoms appeared and gradually progressed. EBV-encoded RNA, detected using in situ hybridization, disclosed the presence of EBV in liver and bone marrow tissue, and real-time PCR revealed the presence of EBV in the cerebrospinal fluid (CSF) and serum. CD3+CD4+CD8-CD56- T-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…To date, CNS involvement in patients with CAEBV has hardly been reported [6][7][8][9]. Although two autopsy cases of CAEBV with CNS lesions have been reported [8,9], details of neuropathological findings were not described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, CNS involvement in patients with CAEBV has hardly been reported [6][7][8][9]. Although two autopsy cases of CAEBV with CNS lesions have been reported [8,9], details of neuropathological findings were not described.…”
Section: Discussionmentioning
confidence: 99%
“…Although two autopsy cases of CAEBV with CNS lesions have been reported [8,9], details of neuropathological findings were not described.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EBV infection often present with liver disturbance. While IM is often accompanied by mild hepatitis, several groups have reported that patients with CAEBV progressed to hepatic failure, 2,18 and that 7.5–33% of patients with CAEBV died due to hepatic failure 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…EBV is a ubiquitous herpes virus that usually causes asymptomatic infection during early childhood. Infectious mononucleosis (IM) is a symptomatic acute EBV infection occurring more often in adolescents and young adult than in children, and is usually a benign self‐limiting disease 1,2 . It is thought that EBV remains latent for life in the B cells of normal hosts after primary infection, 3,4 and that T‐cell immunity, including immunity against cytotoxic T cells and natural killer (NK) cells, primarily regulates the proliferation of EBV‐infected B cells 1,3 …”
mentioning
confidence: 99%
See 1 more Smart Citation